AKTIVITAS PENGHAMBATAN ENZIM α-GLUKOSIDASE EKSTRAK DAN FRAKSI ETIL ASETAT DAUN SALAM (Syzygium polyanthum (Wight) Walp.) - Aufa Ali Fajar Nanda Nasukha; Lilik Sulastri; Partomuan Simanjuntak (PROSIDING SEMINAR KIMIA, 2023)
Diabetes Mellitus is a chronic disease caused by the inability of the pancreas to produce insulin which is characterized by hyperglycemia. One of the therapies used to lower blood glucose levels is drugs that have a mechanism to inhibit the α-glucosidase enzyme, so that it can delay the glucose absorption in the digestive tract. One of the plants that has the potential to inhibit the α-glucosidase enzyme is bay leaf. The intention of this study was determine the activity of ethyl acetate extract and chromatographic fraction of bay leaf in inhibiting the α-glucosidase enzyme. A liquid-partition process from 96% ethanol extract was carried out to obtain ethyl acetate extract. The ethyl acetat extract was separated by fractionation using chromatography and TLC with pNPG substrate and acarbose positive control. The inhibitory activity testing of the α-glucosidase enzyme was executed using an ELISA reader with a wavelength of 405 nm. The result revealed that the ethyl acetate extract had inhibitory activity of the α-glucosidase enzym with an IC50 of 79,65 ppm. The F-5.5 fraction was the best fraction with an IC50 value of 18,99 ppm. The acarbose activity in inhibiting the α-glucosidase enzyme had an IC50 value of 18,05 ppm. Keywords : α-glucosidase, antidiabetic, Salam leaves, Syzygium polyanthum